Territorial lords in Bosnia and their selection of missionaries for different diplomatic missions - Smiljanić, Aranđel (Historical Thought, 2025)
The diplomatic activity of Bosnian territorial lord was omnipresent and diverse. Some of the territorial lord were engaged in multiple diplomatic activities. That is the reason for the classification of the activities, which was done by a criterion based on their complexity. Apart from the above-mentioned, this paper aims to address the number of responsibilities assumed by diplomats, the membership and composition of the diplomatic missions and activities conducted to prepare the ground for future negotiations. These questions are interrelated and should be treated as a whole. Details of the missions together with the drawing of adequate conclusions, comprise the scrutiny of the paper. The author used published historical sources and adequate literature for the purpose of the research presented in the paper.